Low-carbon preparation of blast furnace burden from iron ore concentrates via cold-bonding process: New insights into the effect of concentrate type - Xiaolong Wang; Zhiyun Ji; Xiaohui Fan; Min Gan; Shaochun Li; Shengxuan Fan; Zengqing Sun; Jiaming Lv; Yanqing Du; Jiasheng Li; Ying Yu (Minerals Engineering, 2026)

Microalgae-based biogas slurry treatment integrated with sustainable aviation fuel production: from waste to high-value bio-jet fuel - Binbin Zhu; Hongyin Chen; Jing Lv; Wenjun Zhang; Jiaming Liu; Ruirui Liu; Bishu Qi; Shuhui Li; Chengyu Yang; Xiao Yan; Zijian Xia; Xingliang Xu; et al. (Bioresource Technology, 2026)

Effects of microenvironmental factors on water-insoluble precipitation induced by soybean urease - Chongda Duan; Jiaming Zhang; Yi Luo; Yanzi Sun; Jiaxing Liu; Xiang Lv (Journal of Environmental Chemical Engineering, 2026)

3D mechanical stimulation modulates endothelial exosomes to promote fibroblast activation - Ye Qiu; Zhenkun Lv; Xingying Zhu; Xiaoqian Yang; Jiaming Wan (Tissue and Cell, 2026)

Circadian Rhythm Disorder-Related Dysfunctions are Exacerbated by Aging and Ameliorated by Time-Restricted Feeding - Fengjiao Huo; Qing Liu; Shuaishuai Zhang; Xiaorui Liu; Shuyao Lv; Meili Zhao; Yue Liu; Xiaoqi Zhu; Ce Huang; Shengyu Feng; Hao Wang; Siling Xu; et al. (Neuroscience Bulletin, 2026)

On-demand cinnamaldehyde releasing from gelatin-based active hydrogel activated by lactic acid for pork meat preservation: A novel “one-step-ahead” strategy - Peng Shan; Jiaming Wu; Jian Du; Chenglong Fu; Jinwen Hu; Yehan Tao; Jie Lu; Yanna Lv; Xiaodong Xia; Jijuan Cao; Haisong Wang (Food Chemistry, 2025)

Robust smartphone-assisted cellulosic smart label for real-time monitoring shrimp freshness under low temperature and high humidity conditions - Yilin Wang; Jiaming Wu; Dong Lv; Yehan Tao; Jinwen Hu; Chenglong Fu; Xiaodong Xia; Jijuan Cao; Haisong Wang; Jian Du (Chemical Engineering Journal, 2025)

Nutrient dynamics in the East China Sea: Seasonal changes, budget, and ecological impacts - Xiaosong Zhong; Jiaming Liu; Mengjiao Shi; Xiaotian Liu; Zongqing Lv; Xiangbin Ran (Progress in Oceanography, 2025)

VCU-Net: a vascular convolutional network with feature splicing for cerebrovascular image segmentation - Mengxin Li; Fan Lv; Jiaming Chen; Kunyan Zheng; Jingwen Zhao (Medical & Biological Engineering & Computing, 2025)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Thrust Characteristics of Ducted Propeller and Hydrodynamics of an Underwater Vehicle in Control Motions - Jiaming Wu; Yizhe Dou; Haiyan Lv; Chenghua Ma; Le Zhong; Shunyuan Xu; Xiangxi Han (Journal of Marine Science and Engineering, 2021)
A numerical technique to simulate the hydrodynamic behavior of ducted propellers attached to an underwater vehicle traveling under the mutually interacting flow fields of the vehicle and the propellers is proposed; the hydrodynamic performance of the propellers and the hydrodynamic loading on the main body of the vehicle when it is in different kinds of motion is investigated numerically. In the research, 3D geometric models of the duct, propeller, and main body of the vehicle are first constructed according to their geometrical features. A computational fluid dynamics (CFD) technique based on the hybrid algorithm of dynamic mesh-nested sliding mesh is applied to solve the Navier–Stokes equations that govern the fluid motion around the duct, propeller, and main body of the vehicle when it is in motion. These equations are solved numerically with the CFD code Fluent. With the proposed numerical simulation technique, the hydrodynamic characteristics of the thrusts generated by the ducted propellers and the loading on the main body in the vehicle system under the mutually interacting flow fields are observed. The results of our numerical simulation indicate that the hybrid algorithm of dynamic mesh-nested sliding mesh can simulate multiple degrees of freedom of motion in underwater vehicle systems. In different motion states, the main body exerts a significant influence on the investigated flow fields; during the vehicle motions, negative wakes are formed on both sides of the main body, which lead to a decrease in the thrusts generated by the propellers on both sides. The thrust of the middle propeller is greater than that of the normal single one because of the obstructing effect in the tunnel caused by the main body.

Numerical Simulation of Depth Tracking Control of an Underwater Towed System Coupled with Wave–Ship Interference - Xianyuan Yang; Jiaming Wu; Quanlin Li; Haiyan Lv (Journal of Marine Science and Engineering, 2021)
This paper presents a numerical study of the depth tracking control for an underwater towed system under wave–ship interference condition. To overcome the laminations of ignoring the hydrodynamic factors and wave–ship interference in the existing simulation model for the depth tracking operation of the underwater towed system, a numerical model combining the control system with the computational fluid dynamics (CFD) method based on the overset mesh technique is explored and constructed; the influence of towing ship and head waves is introduced into the numerical analysis of the underwater towed system; a depth control system based on the center of gravity adjustment is proposed and its control characteristics are discussed. The fluid motion around the towed vehicle and the towing ship is governed by the Navier–Stokes equations, and the overset mesh technique is applied for the numerical solution of the equations. The towing cable connecting the towed vehicle and towing ship is governed by the quasi-steady-state catenary equations. The depth tracking controller adjusting the longitudinal position of a shifting weight is constructed based on the proportional–integral–derivative (PID) algorithm. The simulation results show that the numerical simulation system is practicable, and the depth tracking control system is feasible, effective, and robust.